Into the white : the Renaissance Arctic and the end of the image - Heuer, Christopher P. (Zone Books, 2019)
We could never see -- The stars down to earth -- 'A strange quantity of ice' -- The savage episteme -- A Roman interruption : Olaus Magnus, 1555 -- Arctic ink -- There are no fortresses